2020
DOI: 10.3390/en13020358
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of an Intelligent Test System for the Model Test on Deep Underground Rock Caverns

Abstract: The safe disposal of high-level radioactive waste (HLW) is a major issue to ensure environmental protection and the sustainable development of the nuclear energy industry; it is also an equally important issue regarding nuclear safety. Deep-buried geological disposal is recognized worldwide as the safest and most feasible way to protect human beings and the environment. To satisfy the research functions, most underground research laboratories (URLs) for geological repositories are buried deeply, and their layo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…Tis range is basically consistent with the results of other engineering cases [35,36]. At the same time, other scholars conducted some feld tests in Beishan area, and the test results indicated that the excavation disturbed zone is about 1.5 times the cavern's span [37][38][39][40][41][42]. We found the overloading safety factor of X-type cross chamber group.…”
Section: Discussionsupporting
confidence: 84%
“…Tis range is basically consistent with the results of other engineering cases [35,36]. At the same time, other scholars conducted some feld tests in Beishan area, and the test results indicated that the excavation disturbed zone is about 1.5 times the cavern's span [37][38][39][40][41][42]. We found the overloading safety factor of X-type cross chamber group.…”
Section: Discussionsupporting
confidence: 84%
“…Figure 11 presents the typical stress curves measured by pressure cells after excavation. From these results, we concluded the following: The variation of stress after excavation is basically the same as that of previous tests [31,45,53]; namely, the stress measured by the pressure cell and strain brick is basically the same. There is obvious interaction between the chambers during excavation, e.g., the stress curve of the middle part between two parking lots is parabolic rather than a monotonic decreasing trend.…”
Section: Test Results Of Surrounding Rocksupporting
confidence: 77%
“…The properties of the prototype and analogue bolt are listed in Table 3. The physical model was paved, compacted and air-dried layer-by-layer to ensure the integrity and homogeneity of the surrounding rock [48][49][50][51][52][53].…”
Section: Simulation Of the Supportmentioning
confidence: 99%